Unusual Metastases of Hepatocellular Carcinoma to the Heart - KURNIAWAN, ANDREE; LUGITO, NATA PRATAMA HARDJO (Indonesian Journal of Cancer, 2016)
ABSTRACTHepatocellular carcinoma (HCC) is the sixth most prevalent cancer worldwide. Metastasis of HCC to the heart is rare with prevalence on autopsy of less than 6%. There is still limited study evaluated the metastasis of hepatocellular carcinoma to the heart. The aim of this study is to know the prevalence and characteristic of metastasis of HCC to theheart in Indonesia. This retrospective study was conducted in secondary referral hospital in Tangerang county, Indonesia. We evaluated from medical record included baseline characteristic, survival and treatment of HCC and echocardiogram data for diagnosing metastasis to the heart from 2013-2015. There were 5 HCC patients recorded in thelast 3 years. All patients were male with median age 56(53-61) years old. Four patients were diagnosed using transthoracic echocardiograph and the rest using multi sliced CT scan. All patients were having continuous thrombus from inferior cava vein until right atrial. For the conclusion Hepatocellular carcinoma were reported as the cause ofintra-heart metastases in Indonesia. All patients were in late stage.ABSTRAKKarsinoma hepatoselular adalah kanker keenam terbanyak di seluruh dunia. Metastasis karsinoma hepatoselular ke jantung jarang, prevalensi yang ditemukan pada otopsi kurang dari 6 persen. Masih amat jarang studi yang mengevaluasi metastasis karsinoma hepatoselular ke jantung. Tujuan dari studi ini adalah ingin mengetahui prevalensi dankarakteristik metastasis karsinoma hepatoselular ke Jantung di Indonesia. Studi retrospektif ini dilakukan di rumah sakit rujukan tipe B di daerah Tangerang, Indonesia. Kami mengevaluasi dari rekam medis, meliputi karaktersitik dasar, kesintasan, dan terapi karsinoma hepatoselular; serta data ekokardiografi untuk mendiagnosis metastasis ke jantung dari 2013-2015. Terdapat 5 pasien hepatoselular karsinoma pada 3 tahun terakhir. Semua pasien laki-laki dengan usia median 56 (53-61) tahun. Empat pasien terdiagnosis menggunakan ekokardiografi trans torakal dan sisanya menggunakan CT scan. Semua pasien memiliki trombus kontinu dari vena cava inferior hingga atrium kanan. Sebagai simpulan, karsinoma hepatoselular dilaporkan sebagai penyebab metastasis ke jantung di Indonesia. Semua pasien datang pada stadium lanjut.